Investigation of recast and crack formation in laser trepanning drilling of CMSX-4 angled holes - Iralal Morar, Nicolau; Roy, Rajkumar; Mehnen, Jorn; Marithumu, Sundar; Gray, Simon; Roberts, Tracey; Nicholls, John R. (Springer, 2018)
This paper presents an experimental investigation on the influences of laser trepanning drilling process parameters on the recast layer thickness and surface crack formation in CMSX-4 nickel-based superalloy angled holes. The effects of peak power, pulse frequency and the trepanning speed as input parameters were investigated in details by varying the laser drilling conditions using Taguchi orthogonal array-based design of experiment approach. Analysis of variance identifies the significant parameters affecting the output responses. It is found that the output responses are affected mainly by the peak power and trepanning speed. The experimental results reveal that the recast layer thickness increases with the increase of peak power and trepanning speed whereas the crack number density decreases with the increase of peak power only. Pulse frequency has no significant effect on both output responses within the range of values investigated. The knowledge gained in this parametric study could be used to improve the metallurgical characteristics of laser-drilled nickel-based acute angled holes.
Keywords: Laser trepanning drilling; CMSX-4; Recast layer; Surface cracks